The Psychological Impact of Diabetic Limb Problems - R, Bahari (IIUM Medical Journal Malaysia, 2015)
Limb problem is a common complication for patients with diabetes. While the impact of diabetic limb problems on physical health is well known, the psychological impact of the condition is still largely unknown. People with diabetes with or without foot ulcers frequently suffer from major depressive disorder, and this is made worse by the presence of limb complications. Furthermore, depression itself can have negative consequences on the person’s diabetes. Hence, in caring for people with diabetic foot problem, the psychological sequelae must not be overlooked but managed accordingly.